Anna's best friends - Webster, Christy; Disney Storybook Artists (New York : Random House, 2014)
Follows the epic adventures of fearless optimist Anna, who teams up with rugged mountain man Kristoff and his loyal reindeer to rescue her sister, Elsa, from a kingdom of eternal winter.
At head of title: Disney Frozen.
Keywords: Snow -- Juvenile fiction; Princesses -- Juvenile fiction; Sisters -- Juvenile fiction; Snow -- Fiction; Princesses -- Fiction; Sisters -- Fiction; Adventure and adventurers -- Fiction